2021
DOI: 10.1098/rsos.210483
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proton nuclear magnetic resonance method for simultaneous analysis of fluticasone propionate and azelastine hydrochloride in nasal spray formulation

Abstract: A facile, rapid, accurate and selective quantitative proton nuclear magnetic resonance ( 1 H-qNMR) method was developed for the simultaneous determination of fluticasone propionate (FLP) and azelastine hydrochloride (AZH) in pharmaceutical nasal spray for the first time. The 1 H-qNMR analysis of the studied analytes was performed using inositol as the internal standard and dimethyl sulfoxide- d 6 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Different articles have been reported in the literature for the determination of AZE either in dosage form, human plasma or aqueous humor. These articles include: HPLC [27][28][29][30][31] , HPTLC 32,33 , capillary electrophoresis 34 , electrochemical analysis 35,36 , NMR 37 , spectrofluorimetry 22,[38][39][40] and spectrophotometry [41][42][43] .…”
mentioning
confidence: 99%
“…Different articles have been reported in the literature for the determination of AZE either in dosage form, human plasma or aqueous humor. These articles include: HPLC [27][28][29][30][31] , HPTLC 32,33 , capillary electrophoresis 34 , electrochemical analysis 35,36 , NMR 37 , spectrofluorimetry 22,[38][39][40] and spectrophotometry [41][42][43] .…”
mentioning
confidence: 99%
“…Other drugs including: tadalafil [ 17 ], favipiravir [ 18 ] sofosbuvir, ledipasvir, and daclatasvir [ 19 ] were also determined. Additionally, research papers have reported the use of 1H-NMR in the determination of co-formulated drugs or related pharmaceutical compounds like an assay of aspirin, phenacetin and caffeine [ 20 ], an assay of levofloxacin, metronidazole and sulfamethoxazole [ 21 ] and analysis of fluticasone propionate and azelastine hydrochloride [ 22 ] in their combined pharmaceutical preparations. Subsequently, International Pharmacopoeias [ 4 , 5 ] reported qualitative NMR spectroscopy for identification purposes and quantitative NMR spectroscopy to evaluate the composition of polymers and impurities in drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, FLU nasal spray is commonly used to treat antiallergic, anti-inflammatory, and antipruritic effects Fluticasone is official in Indian Pharmacopoeia [24], British Pharmacopeia [25], US Pharmacopoeia [26], and European Pharmacopeia [27]. From the literature review, it is observed that many analytical methods have been developed involving spectrophotometric [28], HPLC [29][30][31][32][33], UPLC-MS/MS [34], NMR [35], HPTLC [36], and stability indicating method [37][38][39] for the estimation of FLU in pharmaceutical formulations. The present manuscript describes a novel, cost-effective, and quick chromatographic separation method for the simultaneous estimation of OLO and FLU in pharmaceutical formulation.…”
Section: Introductionmentioning
confidence: 99%